Haemodynamic characterisation of different endotypes in coronary artery vasospasm in reaction to acetylcholine. (October 2022) - Feenstra, Rutger G.T.; Boerhout, Coen K.M.; Vink, Caitlin E.M.; Woudstra, Janneke; Wittekoek, Marianne E.; de Waard, Guus A.; Appelman, Yolande; Eringa, Etto C.; Marques, Koen M.J.; de Winter, Robbert J.; van de Hoef, Tim P.; Beijk, Marcel A.M.; et al.
Highlights: In reaction to low-dose acetylcholine the negative and equivocal endotype has haemodynamic changes that suggest intact endothelium. In reaction to high-dose acetylcholine the epicardial vasospasm, microvascular vasospasm and equivocal endotype have hemodynamic changes that suggest VSMC-hyperreactivity. The data of our study shows that the equivocal endotype is a form of microvascular spasm in the presence of a normal endothelial function, and therefore these patients might benefit from treatment with anti-vasospastic medication. Abstract: Background: Vasoreactivity testing with high-dose acetylcholine is considered vasospasm provocation and low-dose as endothelial function testing. Aims: To assess the changes in reaction to low- and high-dose acetylcholine in the endotypes of CAS as defined by the Coronary Vasomotor Disorders International Study Group (COVADIS) working group. Methods: Changes in coronary epicardial diameter, coronary blood flow (CBF) and vascular resistance were determined at low-dose acetylcholine. Results: A total of 88 ANOCA patients were included in this analysis. In the negative group (n = 14) incremental infusion of acetylcholine produced a progressive increase in CBF (p = 0.008). In reaction to low-dose acetylcholine, the epicardial vasospasm group (n = 30) is characterised by epicardial vasoconstriction that is significantly more severe compared to the microvascular vasospasm group (p = 0.004)(n = 23). The equivocal group (n = 21) is characterised by an increase in CBF and reduction in vascular resistance that are both significantly different compared to the epicardial vasospasm group (p = 0.036 and p = 0.007, respectively). High-dose acetylcholine decreased epicardial diameter and CBF significantly in the epicardial vasospasm, microvascular vasospasm and in the equivocal group (all p < 0.05. Vascular resistance increased significantly in the epicardial vasospasm group (p < 0.001) and equivocal group (p = 0.009). Conclusion: In reaction to low-dose acetylcholine the negative and equivocal endotype has haemodynamic changes that suggest intact endothelium. In reaction to high-dose acetylcholine the epicardial vasospasm, microvascular vasospasm and equivocal endotype have hemodynamic changes that suggest VSMC-hyperreactivity. These results suggest that the equivocal endotype is a positive test comparable to microvascular vasospasm in the presence of normal endothelial function.